A guide to the properties, choice, therapeutic use and economic value of drugs in disease management (Aukland, New Zealand, 1997)
Th book contains information on therapeutics, discusses the use and effects of drugs within a disease orientated context and so assist clinicians in an understading of drug response indisease states and in the selection of the most appropriate drug and dosage for a particular patient. The book covers the clinical pharmacological basis of therapeutics, with particular emphasis on pharmacokinetics; rational selection and individualised use of drugs; the imfluence of associated disease or intercurrent illness on drug response; diseases caused by drugs; and summary tables and appendices to enable quick reference and correlation of data on individual drugs and classes of drugs. The book also discusses pathophysiological principles and the mode of action of drugs. Additionally, the book provides information on the relevant economic considerations that should be taken into account when understanding treatment of a disease patient, including a part of the disease treatment discussion to provide information on the economic costs of the illness, and the desirable objectives of treatment in relation to the costs of achieving these objectives. The book also discusses the principles of pharmacoeconomic evaluation of drugs and emphasises that drugs should be appreciated for the value they contribute rather than the cost they generate
Keywords: drugs,pharmacology